The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang, Yang; Wang, Tong; Yang, Sen; Wu, Xi; Huang, Wenhua; Fan, Bin; Xia, Junhong; Meng, Zining; Liu, Xiaochun (Frontiers in Marine Science, 2021)
Asynchrony of sexual maturity is a huge limitation in the reproduction of grouper sperm. Cold storage of sperm is an effective method to solve the problem of asynchronization. However, sperms gradually lose their activity with the prolonged storage time in vitro. In order to explore causes, the effects of cold storage on transcriptome, proteome and oxidation resistance of giant grouper sperm were analyzed. Firstly, the absolute RNA quantity and consistent transcripts existed in each spermatozoon were estimated. With the prolonged storage, the RNA quantity gradually decreased both in the cytoplasm and in the mitochondria of the spermatozoon. The decreased transcripts were mainly enriched with energy metabolism and stress response. Similar to RNAs, the absolute protein quantity was also significantly decreased during the storage of sperm. Decreased proteins were mainly enriched with the oxidative phosphorylation pathway. Proteins involved in the oxidative phosphorylation showed a faster degradation rate compared to the average total protein. In addition, the oxidation resistance and adenosine triphosphate (ATP) contents showed a significant decrease in the sperm during storage in vitro. These results implied that damages of transcriptome, proteome, and oxidation resistance have negative effects on the normal functions of sperm, especially their energy metabolism. The present study provides essential foundation for improving the storage of sperm in vitro.